Effects of rumen-protected methionine supplementation on production performance, apparent digestibility, blood parameters, and ruminal fermentation of lactating Holstein dairy cows - Li, Yuanxiao; Wei, Jialin; Dou, Mengying; Liu, Shuai; Yan, Bichuan; Li, Cuiyu; Khan, Muhammad Zahoor; Zhang, Yinghui; Xiao, Jianxin (Frontiers in Veterinary Science, 2022)
This study aimed to evaluate the effects of reducing dietary CP and supplementing rumen protected-methionine (RPM) on production performance, blood parameters, digestibility of nutrients or ruminal fermentation in lactating Holstein dairy cows. A total of 96 lactating cows were randomly assigned to 1 of 2 treatments: diet containing 17.3% CP without RPM (control group; CON; n = 49) or diet containing 16.4% CP and supplemented with 15.0 g/d of RPM (treatment group; RPM; n = 47). No effect was observed in RPM group on milk yield, milk composition and digestibility of nutrients. The results of blood parameters showed that cows in RPM group exhibited lower blood urea nitrogen concentration than in CON group. Rumen microbial crude protein (MCP) was higher in the RPM group compared to the CON group. Ruminal volatile fatty acid (VFA) concentrations were not different between treatments except for butyrate and isovalerate, which were higher in the RPM group than the CON group 2 h after feeding. In conclusion, reducing dietary CP with RPM supplementation did not limit milk yield, milk composition or digestibility of nutrients, but could improve nitrogen utilization, synthesis of MCP and partially increase VFA production 2 h after feeding cows.